Adding a Seat at the Table: A Case Study of the Provider's Perspective on Integrating Community Health Workers at Provider Practices in California - Paulson, Courtney A.; Durazo, Eva M.; Purry, Leigh D.; Covington, Arianne E.; Bob, Bruce Alan; Peters, Rebecca A.; Torchia, Steven; Beard, Baylis; McDermott, Lucy E.; Lerner, Amy; Smart-Sanchez, Joycelyn; Ashok, Mahima; et al. (Frontiers in Public Health, 2021)
Blue Shield of California's Community Health Advocate Program was created to support whole person-health needs by helping individuals of all socio-economic statuses navigate and access community resources, social services, and medical systems. Blue Shield's Health Reimagined team is partnering with medical providers, community resources centers, and community partners to provide intensive person-centered and technology-enabled care to patients, ensuring social needs are met while promoting health equity. A key aspect of the Health Reimagined initiative embeds Community Health Advocates (CHAs) within physician practices serving patients using a payor-agnostic approach, by which Blue Shield aims to increase access to social services and community resources, improve health outcomes, reduce medical costs, and improve overall patient experience. The purpose of this case study is to understand the provider's perspective of embedding a CHA into the care team and the resulting impact on the practice and patients. Blue Shield also sought to identify best practices and barriers of a CHA program within primary and specialty care practices. As part of an ongoing two-year mixed-methods impact evaluation (2019–2021), 10 semi-structured interviews were conducted with a total of 18 providers and office staff at five primary care and specialty practices where CHAs have been embedded. We also conducted two focus groups with the same five CHAs at different points in time. Several themes emerged from the provider, office staff, and CHA interviews. Provider practices found great value in adding a CHA to their care team as the CHA brings flexibility and continuity to patient care. They also found that having access to a CHA with shared life experiences of the communities they served is a key component to the program's success. Providers and staff reported a new understanding of the social determinants of health that impacts a patient's wellbeing with the embedding of a CHA in the care team. Overall, practitioners expressed high satisfaction with the CHA program. During the COVID-19 pandemic, CHAs have been critically important in care, as social needs have increased, and resources have shifted. The CHA program is constantly adapting to address challenges faced by all stakeholders and applying new knowledge to ensure best practices are implemented within the CHA program.